2016
DOI: 10.5897/ajmr2016.7972
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HSV type-1 activity of olive leaves extract crude form acting as a microemulsion dosage form

Abstract: Olea europeae (L.) has been reported to have antibacterial, antifungal and antiviral activities. The aim of the present study is to evaluate antiviral activity of olive leaves extract (OLE) against herpes simplex viruses (HSV) type-1 virus. Screening of antiviral activity was assessed by measuring inhibition of viralinduced cytopathic effect of in vero cells of different OLE fractions that have been successively extracted using solvents of increasing polarities, against HSV type-1 virus. Negligible antiviral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Olive (Olea europaea L.) is one of the most ancient cultivated fruit trees and one of the most important oil-producing crop in the Mediterranean countries [1]. O. europaea extracts of different organs as well as the isolated components have shown a wide spectrum of pharmacological activities like antiallergic [2] anti-inflammatory, immunomodulatory [3], antioxidant [1], antimicrobial [4], antiviral [5], antidiabetic [6], anticancer [7], neuroprotective [8], antihypertensive [9], gastroprotective [10], and collagen production promoter [11].…”
Section: Plant Sourcementioning
confidence: 99%
“…Olive (Olea europaea L.) is one of the most ancient cultivated fruit trees and one of the most important oil-producing crop in the Mediterranean countries [1]. O. europaea extracts of different organs as well as the isolated components have shown a wide spectrum of pharmacological activities like antiallergic [2] anti-inflammatory, immunomodulatory [3], antioxidant [1], antimicrobial [4], antiviral [5], antidiabetic [6], anticancer [7], neuroprotective [8], antihypertensive [9], gastroprotective [10], and collagen production promoter [11].…”
Section: Plant Sourcementioning
confidence: 99%
“…In particular, olive fruit extract (OFE) is a rich source of phenolic molecules, such as hydroxytyrosol, tyrosol, and their secoiridoid derivatives (oleuropein, oleuropein aglycone, and oleanolic acid dialdehydes); verbascoside; lignans; and flavonoids [9], which could act in synergy. Different studies have reported the employment of olive leaf extract (OLE) for the treatment of HSV-1 infections [10][11][12]. Ben Amor I. et al demonstrated the strong anti-HSV-1 effect of OLE by direct virucidal action at a 50% inhibitory concentration (IC50) of 100 µg/mL.…”
Section: Introductionmentioning
confidence: 99%